Housing Policy, Housing Assistance and the Wellbeing Dividend: Developing an Evidence Base for Post-GFC Economies - Beer, A.; Baker, E.; Wood, Gavin; Raftery, P. (Routledge, 2011)
This paper discusses the recent evolution, at a time of turmoil within global financial markets, of Australia’s housing system and considers the effectiveness of housing assistance responses formulated to assist lo- income Australians. Following the Global Financial Crisis (GFC), housing was recast in the public and political consciousness and received substantial policy attention. In this era of rapidly declining housing affordability as well as threats to the supply of housing finance, the Australian Government renewed its approach to housing assistance. The paper examines housing assistance in Australia and assesses individual outcomes in terms of a ‘wellbeing dividend’. It draws upon on a survey of 1700 low-income households to examine individual outcomes for health and wellbeing across three of Australia’s major forms of housing assistance. The research clearly shows that while housing assistance makes a positive contribution to wellbeing, not all forms of assistance are equal.